Penerapan Pembelajaran Matematika Berbasis Desmos pada Materi Fungsi Kuadrat Kelas X SMA Negeri 5 Palangka Raya: Implementation of Desmos-Based Mathematics Learning on Quadratic Function Material for Class X SMA Negeri 5 Palangka Raya - Br Karo, Putri Vanessya Paskaria; Ratnawati, Oktaviana Ainun; Mairing, Jackson Pasini; Putrinanda, Marcia (Anterior Jurnal, 2025)
This research is motivated by the low utilization of technology in mathematics learning. Although students are accustomed to using digital devices such as smartphones, the reality in the field still shows obstacles in optimally implementing technology. Therefore, innovative learning media are needed to utilize technology optimally and attract student learning interest, one of which is through e-learning platforms such as Desmos. This study aimed to determine the effectiveness of the application of Desmos learning media on students' mathematics learning outcomes in the quadratic function material of class X of SMA Negeri 5 Palangka Raya. This research was conducted in May 2025. The subjects of this study were 36 students of class X-2 of SMA Negeri 5 Palangka Raya in the even semester of the 2024/2025 academic year. This type of research uses applied research with qualitative and quantitative data analysis. Data collection techniques were carried out through observations of teacher and student activities, student response questionnaires, and written tests. The results of the study showed that the use of Desmos in learning quadratic functions positively impacted student learning outcomes. The average final test score reached 80.3%, with a classical completion rate of 80%, and student responses to Desmos were in the "good" category, with an average of 72.83%. Based on these results, Desmos has been proven to increase student active engagement and understanding of quadratic functions.